About Pedagogy, Its Words, Concepts and Texts - A. S. Robotova (Высшее образование в России)
The article addresses the problem situation in pedagogy related to the development of linguistic and discursive processes. The author develops her previously expressed ideas about the pedagogue’s linguistic literacy and his(her) responsible attitude to the basic concepts of pedagogy. This paper is an attempt to assess these phenomena and their consequences, to present the author’s subjective view on the problem of using words and concepts, constructing of texts in pedagogy. Theoretical reflections are combined with empirical observations of the author. The importance of aesthetic criteria of the pedagogical text is substantiated. One of the main problems of modern pedagogy is servicing of administrative decisions while the urgent issues of education and upbringing remain on the margins. Pedagogy frequently borrows ideas and concepts from the other fields of knowledge without their pedagogical conceptualization. At present we have a sort of hybrid of psychology and pedagogy when their research areas and subjects are mixed. Pedagogy should give empirical substance to all its abstractions. The proper word must be put on its place – in papers, student’s tutorials, in texts.